2023
DOI: 10.3390/ijms24043613
|View full text |Cite
|
Sign up to set email alerts
|

CBL-Interacting Protein Kinases 18 (CIPK18) Gene Positively Regulates Drought Resistance in Potato

Abstract: Sensor—responder complexes comprising calcineurin B-like (CBL) proteins and CBL-interacting protein kinases (CIPKs) are plant-specific Ca2+ receptors, and the CBL-CIPK module is widely involved in plant growth and development and a large number of abiotic stress response signaling pathways. In this study, the potato cv. “Atlantic” was subjected to a water deficiency treatment and the expression of StCIPK18 gene was detected by qRT-PCR. The subcellular localization of StCIPK18 protein was observed by a confocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…When the water content of the soil in the pots had decreased to 35–40%, it was considered the first day of drought treatment. Samples were collected after a 5-day drought treatment, and three replicates (each containing 10 plants) were employed [ 46 , 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…When the water content of the soil in the pots had decreased to 35–40%, it was considered the first day of drought treatment. Samples were collected after a 5-day drought treatment, and three replicates (each containing 10 plants) were employed [ 46 , 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Drought stress poses a threat to crop productivity and global food security. Yang et al [70] discovered that the potato StCIPK18 gene plays a crucial role in drought tolerance. Overexpression in potatoes improves drought tolerance through decreased water loss, higher relative water content, proline buildup, and enhanced antioxidant enzyme activity.…”
Section: Molecular Insights Into Cbl-cipk-mediated Drought Stress Tol...mentioning
confidence: 99%
“…Manipulating these components through genetic engineering and biotechnological strategies holds great potential for enhancing crop resilience to abiotic stresses. For instance, Yang et al [70] investigated the StCIPK18 gene in potato and demonstrated its crucial role in improving drought tolerance through transgenic approaches. Zhu et al [2] shed light on the roles of CBL and CIPK genes in quinoa's response to abiotic stresses, particularly drought, emphasizing the significance of specific CqCIPK and CqCBL genes.…”
Section: Implications For Crop Stress Resilience and Future Perspectivesmentioning
confidence: 99%
“…Similarly, Yang et al reported that StCIPK18 knockout plants decreased proline contents and antioxidant enzyme activities compared with the wild type under drought stress. Y2H and a bimolecular fluorescent complimentary experiment show StCIPK18 and StCBL4 can interact at the protein level [22].…”
Section: Introductionmentioning
confidence: 99%